(untitled) (Technical Journal, 2023)
The piston of an IC engine bears the number of forces before transferring the force to the crankshaft. The main objective of this study to find out the temperature distribution and deformation in diesel engine piston when it is acted upon by gas pressure and high temperature from burning gas. Aluminum alloy has been chosen for the analysis purpose. Suitable data has been assumed to design the geometry of piston. The analysis of the temperature and deformation due to temperature are performed on FEA based software. The boundary conditions include temperature from burning gases and pressure exerted by gas in piston. The results show the crown of piston has the maximum temperature with value of 196°C and maximum deformation of 0.198mm.